Design and Development of an Intelligent Hybrid Braking System on Industrial Cutting Machines with a Focus on Speed and Safety Enhancement - Baharestantafti, Mohammad Hossein; Jafari Nodoushan, Mohammad Hassan; Sharifi Mehrjard, Zohre (Management Strategies and Engineering Sciences, 2025)
This study was conducted to address the safety challenges in industrial cutting machines (with an emphasis on preventing amputation injuries) by designing and implementing an intelligent hybrid braking system based on the integration of a DC electromagnetic brake and an electromechanical brake. By employing a skin-contact detection sensor with ultra-fast response time and an optimized control circuit, the system is able to, upon detecting danger, within a recorded time of 0.1 seconds (measured using a digital chronograph), inject optimized DC current and simultaneously activate both the electromagnetic and electromechanical brakes, producing a braking torque equivalent to twice the rated torque. Experimental results on a Y90L-4 three-phase induction motor (1.5 kW) showed a 40% and 80% improvement in stopping speed compared to standalone electromagnetic and electromechanical braking systems, respectively. The functional redundancy of this solution (in accordance with IEC 61508 SIL-3) increased the reliability factor to 99.9% and resulted in the complete elimination of amputation injuries in field tests. This system, which has been granted a national patent (Registration No. 024946الف/89) and approved by the National Elites Foundation, represents an innovative solution for safeguarding industrial rotary machinery.